Konsep Maqamat menurut Syekh Nawawi Al-Bantani dalam Kitab Salalim Al-Fudala - Aris Priyanto; Dahri, Harapandi (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
Maqamat is the level of a servant before Allah in terms of worship and spiritual exercises he does. Maqamat also contained in the book Salalim Al-Fudala by Sheikh Nawawi Al-Bantani. The existence of maqamat is very important in the spiritual journey of a salik to get to Allah. With this background, this research aims to: 1). knowing the maqamat concept of Sheikh Nawawi al Bantani in the book Salalim Al-Fuḍala; 2). knowing the maqam’s contained in the Book of Salalim Al-Fudala. The method used in this study is a qualitative research method using descriptive analysis. The results of this study indicate that Sheikh Nawawi Al-Bantani understands maqamat as a will that must be maintained and practiced by a salik. While maqamat according to Sheikh Nawawi Al-Bantani in the book Salalim Al-Fudala are the stages that must be passed by a salik to arrive at Allah by keeping and practicing the nine wills. According to him, the nine wills are repentance, qana'ah, zuhud, learning shari'ah knowledge, keeping sunnah worship, trusting, sincere, uzlah, and keeping time. In addition, there are three kinds of stations offered by Sheikh Nawawi Al-Bantani in the book of Salalim Al-Fudala which are not found in the various stations of other Sufi figures. The three types include; learn shari'ah knowledge, maintain sunnah worship, and keep time. So that these three finally increase the number of maqamat that exist in the discipline of Sufism, where the three maqam are not found in the maqamat concept of other Sufi figures.